Knock, Knock! The Next Wave of Populism Has Arrived! An Analysis of Confirmations, Denials, and New Developments in a Phenomenon That Is Taking Center Stage - Daniele Battista (Social Sciences, 2023)
Giorgia Meloni has long been one of the most important figures on the political scene. Her strength has been, from the very beginning, clear and effective communication, combined with a populist style based on the credibility of her path. Our contribution will attempt to highlight the interweaving that links this discipline to the complex and varied representation of populism. The analyses are based on extensive documentation of data for a period from July 2020 to September 2022, the month in which the vote was held in Italy. This periodisation allowed us to have a broad view of the phenomenon and a consequent linear picture of the state of the art. Moreover, in this way, we were able to cover three years of particularly intense political debate, allowing us to outline the underlying motivations that led to electoral success. Based on existing research, the phenomena are described and then framed in relation to the social and political context in which they were experienced, taking into account the interconnection with communication. In this sense, this contribution aims to introduce a perspective that corrects most analyses in this field, which assume that populist parties have lost ground in Europe with the advent of the pandemic. In fact, this study argues that the communication strategies linked to some of Giorgia Meloni’s political choices, including all forms of populism, have generally succeeded in attracting greater public interest while maintaining the characteristics of a phenomenon with pop traits that favoured its rise.